Optimal conditions for production of extracellular alkaline protease from a newly isolated Bacillus subtilis strain AKRS3 - Ravishankar, Krishnan; Kumar, P. Santhosh; Jacob, Biju; Saravanan, K; Kumar, Muthusamy Ashok; Jacob, Anu (Research in Biotechnology, 2012)
A new strain of alkaline protease producing Bacillus bacterium was isolated from an alkaline soil sample and was characterized. The bacterium was identified as Bacillus subtilis based on 16S rRNA sequencing and phylogenetic tree analysis. The organism was coded as B. subtilis AKRS3. The growth curve of the organism was elucidated by culturing in a basal medium in shake flasks under ambient shaking conditions. The optimal conditions for alkaline protease production were studied by following the monofactorial methodology. Enzyme yield was found to be optimum close to 24 hours, which coincided with the commencement of the stationary phase of the bacterium. A pH of 9.0, temperature of 37o C and agitation speed of 125 rpm were also identified to be optimum for enhanced enzyme yields in shake flasks. An inoculum of 4% v/v with 24 hrs of age was also identified to be ideal for inoculation. Xylose at 2 g/l concentration and beef extract at 1.5 g/l concentration were preferred by the organism for optimum enzyme productivity in the broth. The organism displayed an NaCl tolerance of upto 1 % as optimum. Fe2+ salts at 0.01 % concentration was the preferred metal component in the medium.